Solving reliability redundancy allocation problem in using genetic algorithm - Miriha, Seyyed Masih (2013)
Reliability is a critical subject in engineering field. Increasing system’s reliability is one of the challenging parts of engineering. There are several structures for reliability’s model and one of them is k-out-of-n. Redundancy allocation problem (RAP) is a method to improve system reliability. It is divided into two types, namely, active and standby subsystems. Standby subsystem is divided into Cold, Warm and Hot standby. This study is focused on solving redundancy allocation reliability model by using genetic algorithm (GA). A k-out-of-n reliability’s system is chosen as a case study which was introduced by Coit (2003). Failure rate for each subsystem is dependent on the number of components which is used in the system design. Cold standby and active strategies are used in the redundancy allocation problem (RAP). The study has proposed the best setting for the RAP based on GA. The best setting among the investigated scenarios is the designing with cold standby strategy; experimental results give beta value and number of component for each subsystem. for system reliability at 0.97661 is the best reliability value given by the GA.